Analisis Pendekatan Sosioekonomi pengentasan pengangguran di Daerah Religi - Agus Lukman Hakim; Dirlanudin Dirlanudin; Agus Sjafari; Atik Atiatun Nafisah; Ade Hadiono (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Pandeglang Regency community is an agricultural and religious area located in Banten Province which is adjacent to the Capital City of Jakarta. One serious problem that occurs is unemployment in rural areas. This study aims to analyze the problem of unemployment reality with a socioeconomic approach with a handling approach. This research is a descriptive research. Data collection techniques through questionnaires and interviews, through one stage cluster random sampling method. Secondary data used from related institutions / agencies in the Regional Government of Pandeglang Regency. The analysis technique used is descriptive analysis. The results showed the factors causing unemployment in Pandeglang Regency were due to limited employment, limited business capital; unable to compete in business; low awareness of the community in helping to find (invite) work; low work ethic; inability to capture work / business opportunities; low labor costs; work termination; Closed attitude towards life. The dominant contributing factor to unemployment is the first because of limited employment. Second, it is due to limited business capital and third is due to a low work ethic (lazy character).